المونتاج كفن: - د. فوزي محمد سالم المحمودي (Aljameai, 1970)
المستخلص: تتناول هذه الدراسة موضوع "التلاعب الزمني والمكاني" في فن المونتاج السينمائي كأداة محورية في إثراء السرد البصري وتعميق الأثر النفسي والاجتماعي للأعمال السينمائية. تركز الدراسة على التحليل النظري والتطبيقي لتقنيات التلاعب الزمني والمكاني، ابتداءً من التطور التاريخي لأساليب المونتاج مرورًا بالأسس النظرية والتطبيقات العملية وصولًا إلى تحليل التأثيرات النفسية والاجتماعية على المشاهدين. بينت الدراسة أن التلاعب الزمني يساهم في خلق تفاعل ديناميكي بين المتلقي والسرد البصري، مما يعزز من فهمه العميق للحبكة والشخصيات. كشفت الدراسة أن التقنيات الحديثة في المونتاج الرقمي قد فتحت مجالات واسعة لصناع السينما لإعادة تشكيل البُنى الزمنية والمكانية. أثبتت الدراسة أن التلاعب المكاني، الذي يشمل التحول بين أماكن متباعدة أو دمج مواقع تصوير متعددة، يضفي بعدًا جماليًا إضافيًا. أوضحت الدراسة أهمية التلاعب الزمني والمكاني في تحقيق الأغراض الفنية وإيصال الرسائل الفكرية التي يتبناها العملالسينمائي. أظهرت النتائج أن التلاعب المدروس في الزمن والمكان يلعب دورًا محوريًا في التأثير على مشاعر وتصورات الجمهور، مؤديًا بذلك إلى خلق حالة من الانخراط العاطفي والتأمل الفكري.تؤكد الدراسة على أهمية توظيف هذه التقنيات بشكل استراتيجي ومدروس في الأعمال السينمائية، وتوصي بمواصلة البحث حول تأثيرها العميق على السرد البصري، وخصوصًا فيما يتعلق بتأثيرها على تفاعل الجمهور.Abstract:This study addresses the topic of "temporal and spatial manipulation" in the art of film editing as a pivotal tool in enriching visual narrative and deepening the psychological and social impact of cinematic works. The study focuses on the theoretical and applied analysis of temporal and spatial manipulation techniques, starting from the historical development of montage methods, through theoretical foundations and practical applications, and ending with an analysis of the psychological and social effects on viewers. The study showed that temporal manipulation contributes to creating a dynamic interaction between the recipient and the visual narrative, which enhances his deep understanding of the plot and characters. The study revealed that modern techniques in digital editing have opened wide fields for filmmakers to reshape temporal and spatial structures. The study proved that spatial manipulation, which includes shifting between distant places or merging multiple filming locations, adds an additional aesthetic dimension. The study clarified the importance of temporal and spatial manipulation in achieving artistic purposes and conveying the intellectual messages adopted by the cinematic work. The results showed that the deliberate manipulation of time and space plays a pivotal role in influencing the feelings and perceptions of the audience, thus creating a state of emotional engagement and intellectual contemplation. The study emphasizes the importance of employing these techniques strategically and thoughtfully in cinematic works, and recommends continuing research into their profound impact on visual narrative, especially with regard to their impact on audience interaction.